Estudo do efeito da correlação do alvo no espalhamento de elétrons por moléculas pequenas na faixa de energias baixas e intermediária - Cerqueira Sobrinho, Antonio Moreira de (2004)
In this present work, we have carried out a theoretical investigation on the influence of the target electronic correlation on electron elastic scattering by molecules. Calculated differential, integral and momentum-transfer cross sections on electron elastic scattering by nitrous oxide (N2O) and carbon dioxide (CO2), in low energy range (0.1-20 eV), and carbon monosulfide (CS) and silicon monosulfide (SiS), in low and intermediate energy range (0.1-500 eV) are reported. In this study target wave functions at the Hartree-Fock-Roothaan (HFR) and with single-double excitation configuration interaction (SDCI) levels were calculated. The dynamics of electron-molecule interaction is described by a complex optical potential formed by static, of exchange and correlationpolarization contributions, and for e−CS and e−SiS collisions, we include also the absorption contribution, as the imaginary part of optical potential, to account for the influence of inelastic channels at higher energies. The Schwinger variational iterative method (SVIM) combined with distorted-wave approximation is applied to calculate the scattering amplitudes. The results of cross sections, calculated for both HFR and SDCI functions are presented and compared, along with experimental and/or other theoretical results available in the literature.